Electrifying Educational Games: Enhancing Student Learning with Electrochemistry Board and Card Games - Kurniasih, Dedeh; Sara, Yuni; Kurniawan, Rizmahardian Ashari; Kurniati, Tuti (Education, Science, and Technology International Conference, 2025)
In classrooms where traditional teaching methods prevail, student engagement and comprehension often suffer. Recognizing the significance of innovative learning tools in electrochemistry education, this study set out to evaluate the validity, effectiveness, and practicality of board and card media. Employing an ADDIE-based Research and Development (R&D) approach, we selected 30 students from Class XII MIPA 1 at SMA Muhammadiyah 1 Pontianak using purposive sampling. Validation from experts yielded impressively high scores of 0.90 and 0.83 for the material and media aspects of electrochemistry board and card, respectively. The teaching tools proved highly effective, with an effectiveness score of 0.92, and exceedingly practical, scoring 100% in practicality tests. This research underscores the suitability of the developed board and card media for enhancing electrochemistry learning in high school, particularly within the realm of voltaic cell sub-materials. These findings illuminate the transformative potential of these innovative tools in delivering enriched learning experiences for students.